Effects of solvents on the aromaticity and thermodynamic properties of azacalix[2]arene[2]pyrimidines: A computational study - Tosun, Alihan; Kandemirli, Fatma (European Journal of Chemistry, 2025)
The Harmonic Oscillator Model of Aromaticity (HOMA) indexes for the 2,4,6,8-tetraaza-1(2,4),5(4,2)-dipyrimidina-3,7(1,3)-dibenzenacyclooctaphane (TPB) molecule were calculated in gas, ethanol, n-octanol and water phase. Solvent effects were analyzed with the use of the Integral Equation Formalism Polarizable Continuum Model (IEFPCM) as the default in the self-consistent reaction field (SCRF) method in Gaussian09. The HOMA indexes indicate the presence of highly aromatic pyrimidine and benzyl rings while the parameters for pyrimidine rings slightly decrease and those for the benzyl ring slightly increase with increasing dielectric constant. According to the results, the pyrimidine ring shows the highest aromaticity in the gas phase and a slight decrease in more polar solvents. In contrast, the benzene ring shows an increase in aromaticity as the solvent polarity increases. The HOMO energy of the TPB shifts downward in more polar solvents and the most significant shift occurs in the water phase. The HOMO-LUMO energy gap increases in polar solvents, indicating higher chemical stability and decreased reactivity in these solvents. These findings provide insight into the stability and reactivity of TPB in different phases for potential applications. In addition, apparent thermodynamic properties such as the heat capacity, entropy, enthalpy, and Gibbs free energy of TBP in various solvents were calculated. Using computational simulations, we derive heat capacity equations that exhibit similar quadratic and linear terms in both phases, differing only in their constants. The negative quadratic term leads to a decrease in heat capacity at very low temperatures.